Strategies for Mitigating Complications in High‑Risk Trauma: A Cross‑Sectional Study of Surgical and Orthopaedic Decision‑Making - Waled Faraj Salem Khalefa,; Alkasah, Abdussalam Mohamed Hounki; Alkasah, karima (AlQalam Journal of Medical and Applied Sciences, 2026)
Effective management of high-risk trauma requires rapid clinical decision-making, structured complication mitigation, and coordinated multidisciplinary care. Understanding current practices and barriers among surgeons is critical for improving outcomes. This study was conducted to evaluate clinical decision-making, perioperative complication mitigation strategies, and perceived institutional barriers among surgeons managing high-risk trauma patients. A cross-sectional survey was conducted among 267 surgeons (general, orthopedic, and trauma) assessing demographics, clinical decision-making, complication mitigation, and perceived barriers. Likert-scale responses were analyzed using descriptive statistics and chi-square tests, with p < 0.05 considered significant. The mean age of respondents was 41.6 ± 8.9 years, with 12.3 ± 6.7 years of clinical experience; 78.3% were regularly involved in high-risk trauma care. Clinical judgment was highly valued (mean = 4.32 ± 0.58), and multidisciplinary team involvement was strongly endorsed (mean = 4.47 ± 0.55). Intraoperative safety measures were widely implemented (70.0%, mean = 4.51 ± 0.49), whereas formal risk prediction tools were underutilized (41.9%, mean = 3.21 ± 0.83). Standardized safety practices across the perioperative continuum were associated with perceived reduction in complications (p < 0.001). The most frequently reported barriers included resource limitations (72.7%), staffing shortages (65.2%), and time constraints (61.9%). Enhanced trauma training programs (mean = 4.44 ± 0.52) and standardized protocol implementation (mean = 4.36 ± 0.56) were strongly supported as improvement strategies. Surgeons demonstrate strong engagement in complication mitigation and collaborative decision-making; however, systemic constraints and inconsistent adoption of decision-support tools remain challenges. Implementation of targeted training, standardized protocols, and technological support may enhance outcomes in high-risk trauma care.